Preparation and Properties of Poly(D, L-lactide-co-glycolide-co-ε-caprolactone)/1, 4-Butanediamine Modified Poly(lactide-co-glycolide) Blend Porous Microspheres. Issue 2 (1st February 2022) - Gu, Jiaming; Zhou, Zhihua; Huang, Tianlong; Wu, Wei; Liu, Wenjuan; Zhao, Yanmin; Chen, Ping; Zhou, Ziwei; Wang, Dan; Zhang, Chao; Yi, Meilin; He, Xiao; et al.
Abstract: Composite porous microspheres based on blends of poly(D, L-lactide-co-glycolide-co-ε-caprolactone) (PLGCL) and 1, 4-butanediamine modified poly(D, L-lactide-co-glycolide) (BMPLGA) were prepared by using a combined solvent evaporation and particle leaching technique. The morphologies and porous structure of the PLGCL/BMPLGA microspheres were observed by using scanning electron microscopy (SEM). The in-vitro degradation behaviors and cytocompatibility were studied. The resultant microspheres showed a porous surface and a three-dimensional network structure with interconnecting pores. The changes of morphologies, pH value and mass loss during in-vitro degradation in phosphate buffered solution (PBS) at 37°C indicated that the degradation rate of the BMPLGA was faster than that of the PLGCL in the PLGCL/BMPLGA blends. We suggest the PLGCL/BMPLGA porous microspheres were non-cytotoxic and showed excellent cytocompatibility. We suggest the PLGCL/BMPLGA porous polymeric microspheres have great potential for application for drugs delivery and tissue regeneration.